2012
DOI: 10.4103/0970-9290.107432
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of developmental defects of enamel in children and adolescents with asthma: A cross-sectional study

Abstract: Pediatric asthma patients with severe, early onset asthma are at increased risk of dental enamel defects and therefore require priority dental care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Furthermore, the studies on the topic differ according to design and size of the study population. Therefore, common agreement based on previous results is difficult to obtain 14‐23 …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, the studies on the topic differ according to design and size of the study population. Therefore, common agreement based on previous results is difficult to obtain 14‐23 …”
Section: Introductionmentioning
confidence: 95%
“…Therefore, common agreement based on previous results is difficult to obtain. [14][15][16][17][18][19][20][21][22][23] Previously, the association between the use of asthma drugs and the risk of MIH was examined in the above-mentioned 647 Danish children being 6-8 years of age. 18 We used register-based information on the use of asthma drugs in order to eliminate recall bias, and we found an increased, but not significant, risk of MIH with PEB in children with prescriptions of asthma drugs between the age of 0 and 3 years of age (OR 2.42; 95% CI: 0.70-7.43).…”
mentioning
confidence: 99%
“…In asthmatic patients, the prevalence of DDE was 76.9%, compared to only 26.9% in the control group. 23 In the study by Guergolette et al, 24 89.7% of asthmatic patients had DDE compared to 38.2% in the control group, and it was then concluded that pediatric patients with asthma are at a greater risk for DDE, thus requiring priority dental care. Compared to asthmatic patients, the present study presented a lower prevalence of DDE.…”
Section: Discussionmentioning
confidence: 99%
“…11 It has been demonstrated that asthmatic children consume sugary drinks more often than non-asthmatic children. 12,13 Antiasthmatic medications may also decrease the pH of plaque and saliva, which would make conditions more favorable for caries development. It has also been reported that some inhalers may contain fermentable carbohydrate, such as lactose monohydrate and oral medications in syrup form may contain sugars, this can increase the risk of dental caries.…”
Section: Introductionmentioning
confidence: 99%
“…3 After dental caries, asthma appears to be the most prevalent chronic childhood disease, considered to be a serious global health problem. 4,5 According to global initiative for asthma (GINA) 2008, asthma is a chronic inflammatory disorder of the airways in which many cells and cellular elements play a role. The chronic inflammation is associated with airway hyperresponsiveness that leads to recurrent episodes of wheezing, breathlessness, chest tightness, and coughing, particularly at night or in the early morning.…”
Section: Introductionmentioning
confidence: 99%